Does Access to Finance Alleviates Poverty: A Systematic Review - Bijendra Sharma; Akash Chaurasia (Indonesian Journal of Business Analytics, 2023)
This paper aims to find out the nexus between financial accessibility or access to finance and poverty employing a systematic literature review approach. Two databases, Web of Science and EBSCO, were considered and 7 papers were shortlisted and reviewed using PRISMA guidelines for this study. The study finds out that there is a positive relationship between financial outreach or accessibility and reduction in poverty. But there is a thin relation between financial accessibility and reduction of poverty in urban areas. There is an empirical but bounded evidence between financial accessibility and welfare of households.